MO877PREVALENCE AND PERSISTENCE OF COVID-19 ANTIBODIES IN NEW YORK CITY HEMODIALYSIS CLINIC. (29th May 2021) - Thwin, Ohnmar; Grobe, Nadja; Ye, Xiaoling (Janice); Preciado Rojas, Priscila; Tapia Silva, Leticia M; Kotanko, Peter
Abstract: Background and Aims: Dialysis patients are at higher risk for severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection. Longevity of antibody response to SARS-CoV-2 infection remains unclear. It is reported that maintenance hemodialysis (MHD) patients can mount an antibody response that is similar in intensity and timing to the non-dialysis population. We aim to investigate the prevalence and persistence of antibodies in hemodialysis patients. Method: We measured IgG and IgM antibodies in MHD patients as part of a quality improvement project. Four New York City dialysis clinics participated in this study. Strict policy of RT-PCR testing was implemented in clinics for patients with signs and symptoms of Coronavirus Disease 2019 (COVID-19). Initial antibody testing was done on June 10 and July 13, 2020 (phase 1) and retesting was done for previously positive patients between December 9 and 17, 2020 (phase 2). Upon obtaining verbal consent, 3.5 ml of pre-dialysis blood samples were taken via vascular access. SARS-CoV-2 antibodies were determined using the emergency use authorized Diazyme DZ-Lite SARS-CoV-2 IgM / IgG CLIA assays with 100% sensitivity and 98% specificity. Detection of formed immune-complexes is achieved with N-(4-amino-butyl)-N-ethyl-isoluminol; the luminescence signal is reported as units per ml (AU/ml), values ≥ 1.00 AU/ml are considered as "reactive" and < 1.00 AU/ml as "non-reactive." Results: A total of 429 MHD patients were studied in phase 1. Antibodies were present in 130 (30.3%) and only 55 patients with Covid-19 diagnosis confirmed by RT-PCR test were reactive for IgG antibodies. The time to antibody testing was 73 days (median 77; range 30-111) days. In the phase 2 antibody testing, IgG antibodies were only detected in 47 patients (85.5%) 242 days (median 245, range 204 to 268) after clinical diagnosis of Covid-19. Between the two phases of antibody testing, the luminescence signal declined by 40.9 AU/mL (95% confidence interval 31.5 to 50.3) from 54.1±45.3 to 13.2±20.9 AU/mL (P<0.0001 by paired t-test; Figure 1 ). In univariate logistic regression, a higher number of days between clinical diagnosis of COVID-19 and the second antibody measurement was associated with a lower seropositivity rate (odds ratio 0.929, 95% confidence interval 0.864 to 0.998, P=0.044). Antibody persistence was not associated with age, gender, race, and ethnicity. Conclusion: We observed that about 6 out of 7 MHD patients maintain SARS-CoV-2 antibodies over 6-9 months but there is a significant decline of IgG level. The time between clinical diagnosis and IgG testing was associated with IgG decline. Follow up study to understand antibody dynamics in MHD population is a crucial step once vaccines become available.